Outcome of liver transplantation in patients with hereditary bleeding disorders: a single centre UK experience. (1st March 2016) - Murthy, V.; Murray, D.; Hebballi, S.; Bramhall, S.; Lester, W.; Mutimer, D.; Wilde, J.
Abstract : Introduction: Patients with hereditary bleeding disorders who have developed end‐stage liver disease as a consequence of hepatitis C infection (HCV) acquired from factor concentrates prior to the introduction of viral inactivation continue to be referred for liver transplantation. Methods: A retrospective review of case notes and electronic records was performed on all patients with bleeding disorders who have undergone liver transplantation at the University Hospital Birmingham (UHB). Results: Between 1990 and 2014, 35 liver transplants have been performed in 33 patients with hereditary bleeding disorders. The indication for transplantation was mainly end‐stage liver disease secondary to HCV. Five patients had human immunodeficiency virus (HIV) co‐infection. No excess mortality due to bleeding occurred in the peri or postoperative period. Median overall survival post transplant is 9.7 years. Overall survival rates at 1, 3 and 5 years are 90%, 72% and 64% respectively. The predominant cause of mortality was liver failure secondary to either recurrent HCV or recurrent hepatocellular carcinoma (HCC). The median overall survival in patients with HIV co‐infection is shorter than in those with mono‐infection but this is not statistically significant. Patients with a pre‐existing HCC had a statistically significant shorter survival (2.4 years vs. 13.6 years, P  = 0.007). Conclusion: Liver transplantation has become an accepted treatment option for patients with hereditary bleeding disorders and HCV associated end‐stage liver disease with survival rates similar to non‐bleeding disorder patients.